The rational choice of implementing Hamis Batar traditional rituals by the community of Rabasahain Village - Hildigardis M. I. Nahak; Blajan Konradus; Dasma Damanik (Goodwood Publishing, 2021)
Purpose: In this study, this research aimed to find out the process of implementing the Hamis Batar rite and how it means for the people of Rabasahain Village. Research methodology: The approach used in this study is qualitative. The analysis in this study uses the Rational Choice Theory. Respondents were selected by purposive sampling. 6 respondents are consisting of Village Head, 1 Traditional Head and 4 ordinary people who are often involved in the implementation of the Hamis Batar Ritual. Results: The Hamis Batar ritual is a traditional event carried out by the Rabasahain community as a form of gratitude to the creators and ancestors for the harvest obtained and its implementation depending on the agreement of the Fukun, Katuas And Ferik of the traditional house, as well as the readiness of corn as an offering. Based on the research, it can be concluded that the Hamis Batar ritual is categorized as a rational activity because it is considered to have a function and purpose for society. Limitations: This research does not cover more details about the Hamis Batar Ritual. This research only focuses on explaining the process of the Hamis Batar Ritual in brief and showing the ritual as a rational activity. Contribution: This research becomes scientific information for social science and culture. Keywords: Rituals, Indigenous activities, Rational choice theory